We start with the equation:
\[
2.25 t + 5 = 13.5 t + 14
\]
To isolate the terms involving \( t \), we rearrange the equation:
\[
2.25 t - 13.5 t = 14 - 5
\]
Step 2: Simplifying the Equation
This simplifies to:
\[
-11.25 t = 9
\]
Step 3: Solving for \( t \)
Next, we divide both sides by \(-11.25\):
\[
t = \frac{9}{-11.25}
\]
Converting \( -11.25 \) to a fraction gives us:
\[
t = \frac{9}{-\frac{45}{4}} = \frac{9 \cdot 4}{-45} = \frac{36}{-45} = -\frac{4}{5}
\]
Step 4: Final Result
Thus, the solution for \( t \) is:
\[
t = -\frac{4}{5}
\]